2016
DOI: 10.1038/am.2016.173
|View full text |Cite
|
Sign up to set email alerts
|

Newtype large Rashba splitting in quantum well states induced by spin chirality in metal/topological insulator heterostructures

Abstract: In a two-dimensional system without inversion symmetry, such as a surface or interface, the potential-asymmetry-induced electric field can create the Rashba effect, which is spin-band splitting caused by spin-orbit coupling (SOC). On the basis of Rashba splitting, several promising spintronic devices, such as the Datta-Das spin transistor, have been designed for manipulating spin precession in the absence of a magnetic field. Rashba splitting can be created in several metal quantum well states (QWSs), such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Many innovative technical solutions have been proposed based on the Bi 2 Se 3 topological insulator interfaced with metal Ag as an electrode, functional layer, or cocatalyst. ,,, All these initial investigations do not take in account aging of the systems due to possible chemical changes on the interfaces. They might identify the presence of Ag immediately after the synthesis but do not repeat the same analysis after some time has passed to confirm the chemical stability of the interface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many innovative technical solutions have been proposed based on the Bi 2 Se 3 topological insulator interfaced with metal Ag as an electrode, functional layer, or cocatalyst. ,,, All these initial investigations do not take in account aging of the systems due to possible chemical changes on the interfaces. They might identify the presence of Ag immediately after the synthesis but do not repeat the same analysis after some time has passed to confirm the chemical stability of the interface.…”
Section: Discussionmentioning
confidence: 99%
“…Some theoretical papers, involving the metal/TI systems, have recently been published, while experimental studies are very rare. Mostly they focus on systems with extremely low coverage, that is, quasi-isolated metal atoms adsorbed on a TI surface. , Only recently Walsh et al have published the first systematic research on Au, Pd, Ir, and some transition metals interfaced with Bi 2 Se 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These calculations showed that for Au and graphene the spin-momentum locking is maintained for the TSS [6], while Pd and Pt should exert a stronger interaction with the TI surface resulting in delocalization of the TSS and poor spin-momentum locking. In another study, a theory predicts that Ag and Au thin layers on Bi2Se3 have large Rashba splitting and high spin polarization of the Ag quantum wells, which give a great potential for development of spintronic devices [7]. Finally, calculations foresee also that the presence of robust TSS affect the adsorption properties of metals (bi-layer of Au, and clusters of Au, Ag, Cu, Pt, and Pd) supported on TI [8] [9], in some cases resulting in the enhancement of the catalytic processes.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent ARPES measurements reveal that the strength of Rashba splitting on the three-dimensional (3D) TI, Bi2Se3, surface can be tuned by involving adsorbates, such as Pd and Cs [19,21]. Moreover, a recent theoretical work suggests that a new kind of large Rashba splitting states is expected to appear particularly at the Bi2Se3/Ag interface induced by the spin chirality of TSSs, which possess stronger spin polarizations than TSS in Bi2Se3 [27]. Therefore, this emerging RSS are promising to generate spin currents more efficiently.…”
mentioning
confidence: 99%